Identification and characterization of nuclear, cleaved amplified polymorphic sequence (CAPS) loci in Irvingia gabonensis and I. wombolu, indigenous fruit trees of west and central Africa - LOWE, A. J.; RUSSELL, J. R.; POWELL, W.; DAWSON, I. K. (Molecular ecology, 1998)
Irvingia gabonensis and I. wombolu (Irvingiaceae) are economically important fruit trees native to moist tropical forest in west and central Africa. Currently, both species are the subject of intensive research due to their potential for incorporation in agroforestry systems and concerns over high rates of deforestation in their native ranges. To inform evaluation and conservation programs, it is necessary to understand the partitioning of genetic diversity in both species. Techniques such as RAPDs are often applied to previously unstudied taxa because no sequence information is required. However, these markers are dominant and of limited utility for studying the reproductive ecology of species. In addition, such markers do not provide phylogenetic information which offers extra insights into contemporary patterns of genetic variation within taxa and can provide evidence of origin and ancient gene flow. Here, we describe the development of anonymous, nuclear, cleaved amplified polymorphic sequences (CAPS), which have been successfully applied to a range of phylogeographic and population genetic questions, for I. gabonensis and I. wombolu.